RELEVANSI MASLAHAH DALAM MENIMBANG KEWAJIBAN NAFKAH SKINCARE DAN KOSMETIK BAGI ISTRI: PERSPEKTIF ULAMA KLASIK DAN KONTEMPORER DALAM RUMAH TANGGA MODERN - Mochamad Rafi Asy Syauqi (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2025)
The fulfillment of maintenance in the household is one of the main pillars in maintaining the harmony of the husband and wife relationship. In the context of modern society, the question arises whether the needs of skincare and cosmetics for wives are included in the category of mandatory maintenance according to Islamic law. This study aims to analyze the perspectives of classical and contemporary scholars regarding the husband's obligation to meet such needs. The method employed is library research, involving an examination of fiqh literature from the four major schools of Islamic jurisprudence as well as contemporary scholarly views. The results of the study show that there are differences in views among scholars. The Hanafiyah, Shafi'iyah, and Hanabilah schools of thought generally do not require cosmetics as part of maintenance, unless it is related to basic hygiene or the husband's request. Meanwhile, the Malikiyah school states that the husband is obliged to fulfill it if he has the financial ability and it becomes a habit that supports harmony. Contemporary scholars such as Yusuf Qardhawi argue that if skincare is used for treatment or skin care, it can be categorized as nafaqah. This study concludes that cosmetic needs are not absolutely the husband's obligation, but can be a form of attention and affection in fostering a harmonious household. Therefore, healthy communication between spouses is needed to agree on the limit of maintenance according to the context and ability of each.